Electromyographic and Electroglottographic Biofeedback in the management of voice disorders: Systematic Review - Abril-Rodríguez, Sofía; Herrero, Ricard (Revista de Investigación en Logopedia, 2022)
Electromyography and electroglottography are exploration techniques that, combined with biofeedback, enable muscle adjustments in the issuer to improve phonatory function. We therefore intend to determine the effects of electrographic biofeedback to increase or decrease the tone in the muscles that involves indirectly or directly in the production of the voice, to identify the effects of electroglottographic biofeedback to produce changes in the vibratory pattern of the vocal folds and, finally, to determine the frequency of biofeedback in vocal treatment, starting from systematic review in papers published since 2000 in speech therapy and laryngological journals. The analysis of the studies obtained in the documentation process suggests that the use of electromyographic and electroglottographic biofeedback can produce lasting changes over time in the vibratory pattern of vocal folds and in the muscle activity of vocal production, so that could be a useful instrument added to vocal intervention based on evidence. The data in relation to frequency of use of this instrument, however, does not seem conclusive.